LC-MS/MS method for determination of cyclin-dependent kinase inhibitors, BP-14 and BP-20, and its application in pharmacokinetic study in rat - Široká, Jitka; Čečková, Martina; Urbánek, Lubor; Kryštof, Vladimír; Gucký, Tomáš; Hofman, Jakub; Strnad, Miroslav; Štaud, František (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2018)
N2-(4-Amino-cyclohexyl)-9-cyclopentyl-N6-(6-furan-2-yl-pyridine-3-ylmethyl)-9H-purine-2,6-diamine (BP-14) and 2-(5-{[2-(4-amino-cyclohexylamino)-9-cyclopentyl-9H-purine-6-ylamino]-methyl}-pyridine-2-yl)-phenol (BP-20) are novel cyclin-dependent kinase inhibitors, structurally related to roscovitine, with significant biological activity. A simple, selective and sensitive liquid chromatography - tandem mass spectrometry method for determining them in rat plasma, using roscovitine as an internal standard, was developed and validated. Chromatographic separation was performed in reversed phase mode on Acquity BEH C18 column (100 × 2.1 mm, 1.7 μm) by gradient elution with mobile phases composed of 15 mM ammonium formate pH 4.0 and methanol at flow rate 0.25 mL/min at 40 °C. The analytes were detected based on their characteristic multiple reaction monitoring transitions in positive electrospray ionization mode m/z 473.07 > 157.93 for BP-14, m/z 499.62 > 184.2 for BP-20 and m/z 355.5 > 90.86 for internal standard. In plasma the method provided good linearity within the entire concentration range: 1-10,000 nmol/L (r2 = 0.9989) for BP-14 and 10-25,000 nmol/L (r2 = 0.9994) for BP-20; the limit of detection was 0.6 nmol/L for BP-14 and 6.1 nmol/L for BP-20. Validation was also performed in bile and urine. The results of validation fit within the acceptance limits following European Medicines Agency guidelines. The method was applied in a pharmacokinetic study of BP-14 and BP-20 in vivo in rats following intravenous and intraduodenal administration including plasma pharmacokinetics, tissue distribution and excretion (renal and biliary). Both compounds showed low bioavailability after intraduodenal administration (0.630 and 1.58% for BP-14 and BP-20, respectively). Distribution into all the analyzed tissues (brain, lungs, liver, kidney, spleen, muscle, adipose tissue) was observed 3 h after single dose administration, the highest and lowest concentrations being reached in the adipose tissue and brain, respectively. The biliary excretion of the parent BP-14 and BP-20 compounds accounted for 4.81% and 10.6% of the doses, respectively, and renal excretion for <0.5% in both cases. The obtained results represent pilot knowledge for further development of a new generation of compounds with strong anticancer activities.
Keywords: limita detekce; Protein Kinase Inhibitors; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie; Cyclins; Tissue Distribution; zvířata; Molecular Structure; Hepatobiliary Elimination; Administration, Intravenous; tandemová hmotnostní spektrometrie; Cyclin-dependent kinase inhibitor; intravenózní podání; Limit of Detection; Tissue distribution; hepatobiliární exkrece; Antineoplastic Agents; Animals; lidé; Reproducibility of Results; potkani Wistar; 2-Aminopurine; biologická dostupnost; reprodukovatelnost výsledků; Calibration; BP-20; kalibrace; Pharmacokinetics; BP-14; Rats; tkáňová distribuce; Male; inhibitory proteinkinas; Biological Availability; Humans; mužské pohlaví; molekulární struktura; 2-aminopurin; krysa rodu Rattus; Rats, Wistar; Structure-Activity Relationship; Chromatography, High Pressure Liquid; cykliny; protinádorové látky; vztahy mezi strukturou a aktivitou